Intelligent Transportation Systems for Electric Vehicles - Ferreira, Joao (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The Special Issue of Energies on the subject area of "Intelligent Transportation Systems (ITS) for Electric Vehicles (EV)", covers new work on EV and associated topics like charging process, smart grids, emerging ITS for EV and applications for electromoV market penetration with an increase of 60% per year, associated challenges of the charging process and system and changes in the energy market and grid. EV is associated with sustainability and the EU has committed to reducing CO2 emissions by 37.5 percent by 2030. The charging process and open energy market with renewable energy create interesting research problems where IoT and intelligent systems play an essential role in the flexibility of the EV charging process and the EV operation.bility. Considering EV market penetration with an increase of 60% per year, associated challenges of charging process and system and the change on the Energy market and Grid. EV is associated with sustainability with the commit of EU in, aiming to reduce CO2 emissions by 37.5 percent from 2021 to 2030. Charging process and open energy market with renewable energy creates interesting research problems where IoT and Intelligent System plays an essential role in the flexibility of the EV charging process and the EV operation.